Prioritizing zoonotic diseases in Ethiopia using a one health approach - Emily G. Pieracci; Aron J. Hall; Radhika Gharpure; Abraham Haile; Elias Walelign; Asefa Deressa; Getahun Bahiru; Meron Kibebe; Henry Walke; Ermias Belay (One Health, 2016)
Background: Ethiopia has the second largest human population in Africa and the largest livestock population on the continent. About 80% of Ethiopians are dependent on agriculture and have direct contact with livestock or other domestic animals. As a result, the country is vulnerable to the spread of zoonotic diseases. As the first step of the country's engagement in the Global Health Security Agenda, a zoonotic disease prioritization workshop was held to identify significant zoonotic diseases of mutual concern for animal and human health agencies. Methods: A semi-quantitative tool developed by the US CDC was used for prioritization of zoonotic diseases. Workshop participants representing human, animal, and environmental health ministries were selected as core decision-making participants. Over 300 articles describing the zoonotic diseases considered at the workshop were reviewed for disease specific information on prevalence, morbidity, mortality, and DALYs for Ethiopia or the East Africa region. Committee members individually ranked the importance of each criterion to generate a final group weight for each criterion. Results: Forty-three zoonotic diseases were evaluated. Criteria selected in order of importance were: 1)severity of disease in humans, 2)proportion of human disease attributed to animal exposure, 3)burden of animal disease, 4)availability of interventions, and 5)existing inter-sectoral collaboration. Based on the results from the decision tree analysis and subsequent discussion, participants identified the following five priority zoonotic diseases: rabies, anthrax, brucellosis, leptospirosis, and echinococcosis. Discussion: Multi-sectoral collaborations strengthen disease surveillance system development in humans and animals, enhance laboratory capacity, and support implementation of prevention and control strategies. To facilitate this, the creation of a One Health-focused Zoonotic Disease Unit is recommended. Enhancement of public health and veterinary laboratories, joint outbreak and surveillance activities, and intersectoral linkages created to tackle the prioritized zoonotic diseases will undoubtedly prepare the country to effectively address newly emerging zoonotic diseases.